2020
DOI: 10.1016/j.jiph.2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of MERS-CoV in healthy adults in western Saudi Arabia, 2011–2016

Abstract: a b s t r a c tBackground: The Middle East respiratory syndrome coronavirus (MERS-CoV) is a newly recognized zoonotic coronavirus. Current evidence confirms the role of dromedaries in primary human infections but does not explain the sporadic community cases. However, asymptomatic or subclinical cases could represent a possible source of infection in the community. Methods: Archived human sera (7461) collected between 2011 and 2016 from healthy adult blood donors from 50 different nationalities in the western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…Asymptomatic and subclinical rates of MERS-CoV are generally higher, but available serosurveys lack the power to draw strong inference about age trends. A large serosurvey conducted across Saudi Arabia found that the age of seropositive individuals was significantly lower than the age of clinical cases 134 , while another conducted across multiple countries in Africa and Asia found no trend in seroprevalence with age 135 . Studies of risk factors within camel workers have either not addressed age as a risk factor 136,137 or not found an association 138 .…”
Section: Level Of Evidencementioning
confidence: 98%
“…Asymptomatic and subclinical rates of MERS-CoV are generally higher, but available serosurveys lack the power to draw strong inference about age trends. A large serosurvey conducted across Saudi Arabia found that the age of seropositive individuals was significantly lower than the age of clinical cases 134 , while another conducted across multiple countries in Africa and Asia found no trend in seroprevalence with age 135 . Studies of risk factors within camel workers have either not addressed age as a risk factor 136,137 or not found an association 138 .…”
Section: Level Of Evidencementioning
confidence: 98%
“…A recent study showed that 0.2% of healthy adult blood donors in Saudi Arabia have specific antibodies against MERS-CoV, suggesting the existence of a large number of asymptomatic or mild infections, which may act as an unrecognized source of infection. 22 Similar high numbers of asymptomatic or minimally symptomatic infections have probably occurred during the SARS epidemic. Although the exact incidence of such asymptomatic infection remains unknown, a metaanalysis of SARS data showed overall seroprevalence rates of 0.1% for the general population and 0.23% for health care workers.…”
Section: Comparison Of Covid With Other Coronavirus Outbreaksmentioning
confidence: 93%
“…Camel to human transmission of MERS-CoV may occur through contact with camels, unpasteurized camel milk, and medicinal use of camel urine, 19 but human to human transmission of the virus also occurs and has been documented in health care workers. 20 MERS has a much higher case fatality rate (about 35% for the 2500 patients with clinical infections 21,22 ). All 3 diseases (SARS, MERS, and COVID-19) have similar, but not identical, clinical manifestations, spanning the entire range from mild flu-like symptoms to severe pneumonia and acute respiratory distress syndrome.…”
Section: Comparison Of Covid With Other Coronavirus Outbreaksmentioning
confidence: 99%
“…The current studies were commissioned by the Directorate of Veterinary Services of Kenya to determine the seroprevalence and geographic distribution of seropositive camels using ELISA tests and quantify the associations between MERS-CoV seropositivity in camels and host or environment variables. However it should be noted that the serologic evidence of MERS-CoV antibodies is an evidence of exposure and does not equate the measure of true prevalence of MERS-CoV infection in camels( Müller et al, 2014 )( Degnah et al, 2020 ). Outputs of these studies were expected to inform the development of efficient and risk-based management strategies against the potential risk of MERS-CoV transmission to humans.…”
Section: Introductionmentioning
confidence: 99%